2020
DOI: 10.1186/s13756-020-00721-w
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in critical care units at Bugando Medical Centre, Mwanza, Tanzania: the role of colonization and contaminated cots and mothers’ hands in cross-transmission of multidrug resistant Gram-negative bacteria

Abstract: Background: Multidrug resistance (MDR) is a major clinical problem in tertiary hospitals in Tanzania and jeopardizes the life of neonates in critical care units (CCUs). To better understand methods for prevention of MDR infections, this study aimed to determine, among other factors, the role of MDR-Gram-negative bacteria (GNB) contaminating neonatal cots and hands of mothers as possible role in transmission of bacteremia at Bugando Medical Centre (BMC), Mwanza, Tanzania. Methods: This cross-sectional, hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
5
23
1
Order By: Relevance
“…This study aimed to assess the prevalence as well as the maternal and neonatal factors of preterm neonatal sepsis in order to contribute to tackling the burden of the illness and its related problems in LMIC. The reported prevalence in this study was found to be lower (21.20%) than previous studies in same setting [11,20] and other parts in East Africa [21] but higher than reports from developed countries [22,23]. The lower prevalence in the current study in this setting could be due to improvement of Infection Prevention and Control (IPC) and the fact that the data for the current study were extracted during the midst of the coronavirus disease 2019 (COVID-19) pandemic, where IPC was largely strengthened.…”
Section: Discussioncontrasting
confidence: 83%
“…This study aimed to assess the prevalence as well as the maternal and neonatal factors of preterm neonatal sepsis in order to contribute to tackling the burden of the illness and its related problems in LMIC. The reported prevalence in this study was found to be lower (21.20%) than previous studies in same setting [11,20] and other parts in East Africa [21] but higher than reports from developed countries [22,23]. The lower prevalence in the current study in this setting could be due to improvement of Infection Prevention and Control (IPC) and the fact that the data for the current study were extracted during the midst of the coronavirus disease 2019 (COVID-19) pandemic, where IPC was largely strengthened.…”
Section: Discussioncontrasting
confidence: 83%
“…Pathogenic potential of E. coli (e.g., E. coli ST131) and K. pneumoniae (e.g., K. pneumoniae ST14), and frequent acquisition of conjugative plasmids encoding for antimicrobial resistance genes (ARGs i.e., ESBL genes) facilitates rapid exchange and dissemination of ARGs in E. coli and K. pneumoniae [ 31 ]. These isolates, ESBL-GNB, colonizing patients are potentially shaded of to contaminate patient’s immediate inanimate surroundings as previous reported [ 32 , 33 ]. Thus increasing the risk of exogenous source of acquiring of healthcare associated infections (HCAIs) from ESBL-GNB among vulnerable patients (immunocompromised and critically ill) associated with increased mortality from treatment failures and limited antibiotic therapeutic options [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 81%
“…This cross-sectional study was conducted in January 2020 at the Catholic University of Health and Allied Sciences (CUHAS) in Mwanza, Tanzania. This study involved 75 presumptive ESBL producing bacteria, showing resistance to third-generation cephalosporins (3GCs), i.e., ceftriaxone and/or ceftazidime, recovered from a previous study [36]. The isolates were identified to species level by physiological and biochemical in-house-prepared tests, as reported in Koneman's Color Atlas and Textbook of Diagnostic Microbiology, 7th Edition.…”
Section: Study Design Duration Setting and Populationmentioning
confidence: 99%
“…For antibiotics susceptibility testing (AST), zone diameters for trimethoprimsulfamethoxazole 25 µg (SXT 25 µg), gentamicin 30 µg (CN 30 µg), ciprofloxacin 5 µg (CIP 5 µg), and meropenem 10 µg (MEM 10 µg) were retrieved from laboratory database of the previous study [36] and interpreted according to CLSI 2020 guidelines [21]. These antibiotics were selected to determine the ability of ESBL-KP and ESBL-EC to resist no β-lactam antibiotics except meropenem and to evaluate the existence of similar phenotypes among ESBL-KP and/or ESBL-EC.…”
Section: Antibiotic Susceptibility Testing (Ast)mentioning
confidence: 99%